The Role of Teachers in Preventing Bullying in Schools Through Collaborative Art Education - Lisna Hikmawaty (Proceeding of the International Conference on Mathematical Sciences, Natural Sciences, and Computing, 2024)
Bullying among students is a serious issue that impacts their mental, physical, and social well-being and disrupts learning activities at school. This study aims to explore the role of teachers in preventing bullying in schools through collaborative art education, utilizing a case study approach at an elementary school. Collaborative art was chosen as a method due to its potential to encourage positive interactions and empathy development among students. Data were collected through classroom observations, in-depth interviews with teachers, and focus group discussions with participating students. The results indicate that teacher-facilitated collaborative art effectively reduces bullying behaviors, fosters harmonious relationships among students, and enhances social skills and empathy. In conclusion, collaborative art education shows promise as a preventive method against bullying, and it is recommended for broader integration as part of character education strategies in schools.